La formation des formateurs à l’ère de la numérisation de la société et de la mondialisation. Les leçons de la pandémie, les apports des sciences cognitives - Denis Legros (Multilinguales)
The covid 19 pandemic has affected more than 1.5 billion pupils and students in 165 countries. It forced teachers to design new teaching methods, with the implementation of distance education as the only alternative to the pursuit of pedagogical continuity. This situation caused many difficulties, in particular the lack of contacts, the technical problems and the difficulties of connection. In addition, many teachers feel that they do not have enough skills in the field of digital technologies. We present some results which show the contributions of cognitive sciences in the field of distance co-learning, which requires specific training of trainers in the era of the digitization of society.